The effect of drying treatment to metabolite profile and cytotoxic potential of Rhizophora apiculata leaves - Mada Triandala Sibero; ANGGUN PUSPITARINI SISWANTO; RUDHI PRIBADI; AGUS SABDONO; OCKY KARNA RADJASA; AGUS TRIANTO; EVAN HANSEL FREDERICK; ALDI PRATAMA WIJAYA; DWI HARYANTI; DESY WULAN TRININGSIH; SASTRA JENDRA HAYUNINGRAT; YASUHIRO IGARASHI (Society for Indonesian Biodiversity, 2020)
Abstract. Sibero MT, Siswanto AP, Pribadi R, Sabdono A, Radjasa OK, Trianto A, Frederick EH, Wijaya AP, Haryanti D, Triningsih DW, Hayuningrat SJ, Igarashi Y. 2020. The effect of drying treatment to metabolite profile and cytotoxic potential of Rhizophora apiculata leaves. Biodiversitas 21: 2180-2187. Coastal communities in Indonesia have utilized Rhizophora spp. leaves as a traditional medicine for many years. The previous studies have succeeded in extracting bioactive compounds from this mangrove after drying treatment, but there is a possibility of the compound decomposition or breakdown. This study aimed to determine the effect of drying treatment on the metabolite profile of R. apiculata leaves which were taken from mangrove forests in Rembang, Central Java. The effect of pre-drying treatment was examined by comparing the metabolites profiles of fresh, oven-dried, and sun-dried leaves crude extracts. Extraction was carried out using maceration method with agitation (110 r.p.m.) for 24 hours in methanol. The metabolite profile was analyzed using high-performance liquid chromatography (HPLC) with diode array detector (DAD) and thin layer chromatography (TLC), while secondary metabolites were studied by phytochemical test. The phytochemical results showed that there were no differences in metabolites in dried and fresh R. apiculata leaves. Crude extract of fresh and oven-dried gave 10 spots on the TLC, while sun-dried crude extract had 9 spots. The one missing spot (Rf value of 0.79) in the sun-dried crude extract might have unstable compounds that are easily degraded or damaged by the sunlight. Moreover, HPLC chromatogram indicated the pre-drying treatment gave alteration to the R. apiculata metabolites that only detected at 400 nm. Cytotoxic assay against P388 murine leukemia cell indicated that oven-dried treatment gave the best anticancer activity with IC50 value of 0.0323 mg/mL.